2008
DOI: 10.1021/ie8008555
|View full text |Cite
|
Sign up to set email alerts
|

Self-Cleaning Test of Doped TiO2-Coated Glass Plates under Solar Exposure

Abstract: Photocatalytic films of TiO2 doped with metal oxides, ZnFe2O4, ZnO, and CuO, were formed on glass plates by the ultraspinning method from Ti(IV) isopropoxide-based sol−gels. To test the self-cleaning properties of TiO2 films on glass, a layer of crystalline fluoranthene, a polycyclic aromatic compound, was placed over the glass by spraying and then exposing it to solar irradiation. The covering of fluoranthene on the 1 wt % metal oxide-doped anatase films was degraded nearly to 100% at 20 h of exposure time. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Photocatalytic materials have gained extraordinary relevance in the last years due to their potential applications in fields such as photo-induced removal of pollutants from air and water, and self-cleaning and antibacterial materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Titanium dioxide (TiO 2 ) is the most widely investigated photocatalyst due to its high photoactivity, low cost, low toxicity and good chemical and thermal stability [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photocatalytic materials have gained extraordinary relevance in the last years due to their potential applications in fields such as photo-induced removal of pollutants from air and water, and self-cleaning and antibacterial materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Titanium dioxide (TiO 2 ) is the most widely investigated photocatalyst due to its high photoactivity, low cost, low toxicity and good chemical and thermal stability [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most photocatalytic coatings are prepared by the post-deposition of the catalyst onto a substrate, such as, glass, textiles, metals or polymers [2,[5][6][7][8][9]12]. In the case of photocatalytic waterborne paints, the photocatalyst (TiO 2 ) usually is one of the components of the paint formulation that is blended with the waterborne dispersed polymer (binder) [3,10,11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticulate TiO 2 has been utilized as an ultraviolet radiation absorber in transparent sunscreen formulations (Nohynek et al ., 2007) and in specialist photocatalytic coatings for glass (Medina-Valtierra et al ., 2009). The environmental chemistry of TiO 2 NPs has been partly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [11] reported the nanosized TiO 2 particles coated on the surface of the SiO 2 layer shows excellent surface wettability with ∼1 • contact angle and 99% transmission despite the high refractive index of TiO 2 . Medina-Valtierra et al [12] demonstrated that the doping of metal in TiO 2 enhancing the self-cleaning property of nanostructured thin film. Ebert and Bhusan [13] studied self-cleaning and transparent properties of SiO 2 , ZnO and ITO nanoparticle coatings on glass and plastic substrates (polycarbonate and PMMA) and found superhydrophobic nature θ c (>150 • ) and high transmittance of visible light (T ∼ 90%) in terms of wettability and transmittance.…”
Section: Introductionmentioning
confidence: 99%